(untitled) (Al-Farooq Journal of Sciences, 2026)
This study examines the dynamics of economic growth in Libya within a rentier economy predominantly dependent on oil revenues, addressing the issue of long-term economic sustainability. Using annual data for the period 1970–2024, the Autoregressive Distributed Lag (ARDL) model is employed to estimate the short- and long-run relationships between GDP and government expenditure, inflation, unemployment, exchange rate, the oil sector, and the non-oil sector, in addition to a dummy variable capturing the structural break of 2011, The Bounds Test confirms the existence of a long-run cointegration relationship among the variables. Long-run estimates indicate that fiscal policy and the exchange rate are the main drivers of growth, while inflation and unemployment exert significant negative effects. The oil sector does not exhibit a direct independent long-run impact, suggesting that its influence is transmitted through fiscal and monetary channels. The error correction model reveals a high adjustment speed of approximately 92% annually, reflecting the rapid transmission of shocks within the rentier structure of the economy, The findings highlight the persistence of the rentier nature of the Libyan economy and the weakness of structural transformation, posing significant challenges to achieving sustainable growth. The study recommends redirecting fiscal policy toward productive investment, strengthening price stability, and accelerating economic diversification to enhance growth sustainability and reduce vulnerability to external shocks.